2019
DOI: 10.1002/cmdc.201800739
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationship Studies of Benzo[b][1,4]oxazin‐3(4H)‐one Analogues as Inhibitors of Mycobacterial Thymidylate Synthase X

Abstract: Since the discovery of a flavin‐dependent thymidylate synthase (ThyX or FDTS) that is absent in humans but crucial for DNA biosynthesis in a diverse group of pathogens, the enzyme has been pursued for the development of new antibacterial agents against Mycobacterium tuberculosis, the causative agent of the widespread infectious disease tuberculosis (TB). In response to a growing need for more effective anti‐TB drugs, we have built upon our previous screening efforts and report herein an optimization campaign o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Among these organisms, many pathogenic ones are found such as Mycobacterium tuberculosis , Helicobacter pylori or Clostridium difficile . For this reason new drugs are being synthesized since the past few years to target FDTS, taking advantage of the differential binding modes of the substrates when compared with normal TS enzyme [19,20,21].…”
Section: Mechanisms Of Action Of Antifolatesmentioning
confidence: 99%
“…Among these organisms, many pathogenic ones are found such as Mycobacterium tuberculosis , Helicobacter pylori or Clostridium difficile . For this reason new drugs are being synthesized since the past few years to target FDTS, taking advantage of the differential binding modes of the substrates when compared with normal TS enzyme [19,20,21].…”
Section: Mechanisms Of Action Of Antifolatesmentioning
confidence: 99%
“…To provide additional experimental support for this notion, we further characterized Psyn ThyX enzymatic activity by performing kinetics measurements in the presence of molecules that bind to the folate binding pocket of bacterial ThyX proteins. These inhibitory studies of Psyn ThyX were performed using H 4 folate (reaction product), CH 2 H 4 folate (substrate), and the tight-binding Mycobacterium tuberculosis ThyX inhibitor 2716 34 , 35 , which all inhibit the NADPH oxidase activity of bacterial ThyX. This analysis revealed that the three bacterial folate analogs tested substantially inhibit Psyn ThyX activity compared to an assay without the addition of any molecule (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To provide additional support for this notion, we further characterized the Psyn ThyX enzymatic activity by performing kinetics measurements in the presence of molecules that bind to the folate binding pocket of bacterial ThyX proteins. These inhibitory studies of Psyn ThyX were performed using H 4 folate (reaction product), CH 2 H 4 folate (substrate), and the tight-binding Mycobacterium tuberculosis ThyX inhibitor 2716 27, 28 , which all inhibit the NADPH oxidase activity of bacterial ThyX. This analysis revealed that the three bacterial folate analogs tested substantially inhibit Psyn ThyX activity compared to an assay without the addition of any molecule (Fig.…”
Section: Resultsmentioning
confidence: 98%